Increased Learning Outcomes of Class VIII D Students in Cultural Arts and Skills Subjects on Illustrated Image Materials Through Project Based Learning Models at SMP Negeri 3 Surabaya - Purnawati, Nina (Indonesian Journal of Contemporary Education, 2019)
This study aims to determine the increase in learning achievement of students of class VIII D of SMP Negeri 3 Surabaya through the application of Project Based Learning (PjBL) methods in Cultural Arts and Skills subjects on illustrated image material. This type of research is classroom action research (CAR) carried out in 2 cycles of action. The research subjects were 38 people consisting of 15 male students and 23 female students. The research data was collected using observation methods and interview methods with assessment rubric instruments. Data from the research results were analyzed using descriptive statistical analysis methods and quantitative descriptive analysis methods. The results of data analysis showed that there was an increase in the learning outcomes of students of class VIII D of SMP Negeri 3 Surabaya from the application of the PjBL method in the first cycle of 78.56% who were in the low criteria experienced an increase in the second cycle to 91.23% classified as high criteria. Thus it can be concluded that the application of the PjBL method can improve the learning outcomes of class VIII D students of SMP Negeri 3 Surabaya on illustrated image materials.